Early life stress and child temperament style as predictors of childhood emotional symptoms: findings from the Longitudinal Study of Australian Children - Lewis, A; Olsson, C (My University, 2011)
Objective: An understanding of individual differences in sensitivity to stressful life events (SLEs) is essential for the development of targeted and more effective approaches to the prevention of mental disorder. Temperament is an important source of individual differences in stress responsivity and therefore a potential driver of sensitivity to social challenges such as family life stressors and maternal depression. The purpose of this study was to determine whether established risk relationships between stressful infant environments and later childhood emotional problems vary as a function of individual differences in temperament style. . Methods: Data was drawn from the Longitudinal Study of Australian Children (LSAC). This study examined 3425 infants, who were assessed at three time points; in their first year, at 2/3 years and at 4/5 years. Temperament was measured using a 12 item version of Toddler Temperament Scale (TTS) and was scored for reactive, shy and impulsive dimensions. Logistic regression was used to model direct relationships and interactions between early life stress, temperament and emotional symptoms at 4 years of age. An adjusted model is presented controlling for socioeconomic status, parental education and marital status. Results: Results suggest that stressful family environments experience in the infant’s first year of life (high vrs low) and high reactive, shy and impulsive temperament styles directly and independently contribute to emotional symptoms in children at 4 years of age. However, contrary to expectations, we observed no evidence of interaction between temperamental and social risks. Conclusions: Both infant temperament and stress exposures are independent and notable predictors later emotional problems in childhood. The risk relationship between stress exposure in infancy and childhood emotion problems did not vary as a function of infant temperament. Implications for preventive intervention and future research directions are discussed
Keywords: Stress; Child Development -- Emotional; Child Development -- Behaviour; Stress -- Life events; Child Development; Disadvantage, adversity and resilience; Childhood and child development; Child Development; Stress; Behaviour; Life events; Emotional; Childhood and child development; Dsiadvantage, adversity and resilience; Adversity and resilience